Perilaku Menyikat Gigi Pada Ibu Hamil Sebelum dan Sesudah Diberikan Penyuluhan Dengan Media Booklet di Puskesmas II Denpasar Barat Tahun 2025 - Dewi, Ni Putu Ayu Asri Andyka; Ratih, Ida Ayu Dewi Kumala; Dwiastuti, Sagung Agung Putri; Agung, Anak Agung Gede (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2025)
Oral and dental health is an important part of overall health, especially for pregnant women who are vulnerable to issues such as gingivitis and dental caries. Low awareness and knowledge of proper toothbrushing techniques among pregnant women contribute to the high prevalence of oral health problems during pregnancy. Therefore, effective education is needed, one of which can be delivered through Booklet media. This study aimed to determine the toothbrushing behavior of pregnant women before and after being given counseling using Booklet media at Puskesmas II West Denpasar in 2025. This research used a descriptive quantitative method with a direct observation approach. A total of 39 pregnant women were selected using accidental sampling. Data were collected through observation sheets before and after the counseling session. Before the counseling, most respondents showed moderate toothbrushing behavior (72%) with an average score of 64,9. After receiving counseling using the Booklet, behavior significantly improved to the good category (90%) with an average score of 90. Counseling using Booklet media proved effective in improving toothbrushing behavior among pregnant women.